Anti-plasmodial effect of plant extracts from Picrolemma huberi and Picramnia latifolia (2018)
ABSTRACT: Background: Malaria is an infectious disease caused by parasites of the genus Plasmodium, of which Plasmodium vivax and Plasmodium falciparum are the major species that cause the disease in humans. As there are relatively few alternatives for malaria treatment, it is necessary to search for new chemotherapeutic options. Colombia possesses a great diversity of plants, which are potential sources of new compounds of medical interest. Thus, in this study the antiplasmodial efect of extracts from two species of plants from the families Simaroubaceae and Picramniaceae(Picramnia latifolia and Picrolemma huberi) was evaluated in vitro and in vivo. These plants were chosen because they contain secondary metabolites with interesting medicinal efects. Results: The ethanolic extracts of both species were highly active with IC50: 1.2±0.19 μg/mL for P. latifolia and IC50: 0.05±0.005 μg/mL for P. huberi. The P. latifolia extract had a stage specifc efect on trophozoites and inhibited parasite growth in vivo by 52.1±3.4%, evaluated at 1000 mg/kg in Balb/c mice infected with Plasmodium berghei. On the other hand, evaluated at 150 mg/kg body weight in the same murine model, the ethanolic extract from P. huberi had an antiplasmodial efect in all the asexual intraerythrocytic stages of P. falciparum FCR3 and inhibited the parasitic growth in 93±32.9%. Conclusions: This is the frst report of anti-malarial activity for these two species of plants. Thus, P. latifolia and Phuberi are potential candidates for the development of new drugs for treating malaria.